Pesantren and Tradition (Study Of Ta'dzim Affiliates in Character Education Al-Ghazali and Thomas Lickona) - Try Heni Aprillia; Agus Harisuddin Masrof; Nur Ahid; Syamsul Huda (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The academic problems of this research stem from the environmental phenomenon of the Pesantren Al-Falah Ploso where the students still respect their Kyai, in other words, the ta’dzim attitude towards the teacher (Kyai) is still very well maintained. This is different from general education institutions in Indonesia. Ta’dzim itself is a form of character education and is a typical pesantren tradition. The research method used is Library Research with a qualitative approach. This study aims to examine the conception of character education of al-Ghazali and Tomas Lickona’s and its relation to the ta’dzim tradition at the Pesantren Al-Falah Ploso. The results showed that the ta’dzim tradition at the Pesantren Al-Falah Ploso was still well sublimated through divine values and human values. This is explained in detail in Al-Ghazali's conception of character education, namely to purify oneself (tazkiyat al-nafs) from despicable traits. Tazkiyat al-nafs is a way to get physical, spiritual, material and spiritual happiness, in this world and the hereafter. Meanwhile, according to Thomas Lickona, there are three important components in building character education, namely: Moral knowing, moral feeling, and moral action.